Analysis of the Application of the Game Gobak Sodor in Character Education for Students at SMKN 4 Semarang - Wara Widi Wigati; Muh. Isna Nurdin Wibisana; Biyarini Koshendarti; Utvi Hinda Zhannisa (Universitas Sebelas Maret, 2024)
Education is the main key to creating civilized humans. Character formation and development is carried out over time in the learning process at school. Efforts to form and develop character can be done through PJOK learning at school. This research aims to analyze character education through the game gobak sodor at SMKN 4 Semarang. The research method used is qualitative with a descriptive type. The research sample was 32 students in class XI Automotive Engineering. Data collection instruments use observation, interviews and documentation. The results of the research show that by implementing the Gobak Sodor game, it can grow and form character values in students, such as cooperation between followers of religions and beliefs, self-confidence, discipline, law-abiding, cooperation, solidarity, deliberation, hard work, creativity, courage, toughness, honesty and responsibility.